2014
DOI: 10.1155/2014/320124
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Iron‐Binding Micelles in Acidic Recombinant Biomineralization Protein, MamC

Abstract: Biological macromolecules are utilized in low-temperature synthetic methods to exert precise control over nanoparticle nucleation and placement. They enable low-temperature formation of a variety of functional nanostructured materials with properties often not achieved via conventional synthetic techniques. Here we report on thein situvisualization of a novel acidic bacterial recombinant protein, MamC, commonly present in the magnetosome membrane of several magnetotactic bacteria, includingMagnetococcus marinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 61 publications
(79 reference statements)
5
18
0
Order By: Relevance
“…These results are in agreement with MamCnts (control) and in the presence of 10 and 60 μg/mL or MamCnts, and c aqueous synthesis without MamC (control) and in the presence of 10 and 60 μg/mL or MamC. The data were normalized to the magnetization values at 300 K. Mms6 data from Wang et al (2012) are plotted for comparison the observations of Kashyap et al (2014) who found that MamC forms micelles in solution and, when a solution of Fe 3+ is delivered, cations bind to the negatively charged surface of the micelle creating a highly concentrated area of Fe 3+ . Magnetite nucleation would then occur preferentially at the surface of the protein micelles, potentially permitting crystal growth with virtually no space limitation.…”
Section: Discussionsupporting
confidence: 81%
“…These results are in agreement with MamCnts (control) and in the presence of 10 and 60 μg/mL or MamCnts, and c aqueous synthesis without MamC (control) and in the presence of 10 and 60 μg/mL or MamC. The data were normalized to the magnetization values at 300 K. Mms6 data from Wang et al (2012) are plotted for comparison the observations of Kashyap et al (2014) who found that MamC forms micelles in solution and, when a solution of Fe 3+ is delivered, cations bind to the negatively charged surface of the micelle creating a highly concentrated area of Fe 3+ . Magnetite nucleation would then occur preferentially at the surface of the protein micelles, potentially permitting crystal growth with virtually no space limitation.…”
Section: Discussionsupporting
confidence: 81%
“…Magnetosome-associated proteins that have been previously characterized, such as Mms6 and, recently, Mms13 (MamC), are also predicted to span the MM. These proteins are expressed in E. coli as insoluble inclusion bodies but, interestingly, can be denatured and refolded into soluble aggregated structures, displaying iron binding capabilities (13,25,26). Coupled with our data, this finding points to a pattern of soluble behavior between various magnetosome-associated membrane proteins.…”
Section: Discussionsupporting
confidence: 76%
“…It was also noted in that study that MamF produced large, SDSresistant, oligomeric species in SDS/PAGE experiments (30), which hinted that these proteins might assemble into aggregated stable species in vitro. Coupled with the work described in this paper and the self-assembly properties of other magnetosome proteins (25,26), we speculate that MmsF and its homologs might assemble within the MM, forming strong packing interactions between themselves. This assembly may tessellate a tightly packed and ordered island of protein within the lipid membrane that could display the active surface loops and termini discussed above in a precise pattern on the interior face of the magnetosome.…”
Section: Discussionsupporting
confidence: 69%
“…This technique has been applied to a broad range of materials systems, including metallic and semiconductor nanoparticles and nanowires [9,, geochemical and biological minerals [8,10,[40][41][42], electrochemical systems (see Ref. [17] for a recent review), protein complexes [40,43,44], viruses, and self-assembling systems of organic films, vesicles, macromolecules, and nanoparticles [10,29,43,[45][46][47][48]. Moreover, nucleation and growth events can be triggered within LP-TEM liquid cells using a number of methods, including mixing of reagents [41], in-diffusion of a gaseous reactant [10], electrochemical reaction [17,18], heating [49], and through the radiolytic effects of the electron beam [50][51][52].…”
Section: Introductionmentioning
confidence: 99%